(untitled) (The Review of Diabetic Studies, 2024)
Healthcare professionals are essential to the efficacy and resilience of the health system. In Saudi Arabia, changes under Vision 2030 have made it more important to have a skilled, multidisciplinary workforce to meet the needs of a growing population, changing health trends, and higher expectations for quality, patient-centered care. This report reviews the roles of physicians, nurses, pharmacists, allied health professionals, public health practitioners, and healthcare administrators in the Saudi healthcare system. It focuses on the value of cooperative effort, workforce development, and system integration in providing excellent care. The article also discusses current challenges and future directions for healthcare professionals in Saudi Arabia, with an emphasis on meeting national health transformation goals.